Learning English through Laptop Approach to Improve the High School Students’ Achievement - Rosmiyati, Evi; Jaya, Aswadi (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2017)
This research presents a critical appraisal of current research on the role technology integration plays in high school students’ literacy achievement. It identifies the gaps within the research through comprehensive analysis. The review develops an argument that the use of laptops in secondary English classrooms has a significant impact upon students’ literacy achievement in both a positive and negative manner. The literature review begins by exploring early research and finds that there is a lack of longitudinal studies regarding laptop integration. This is a result of the trend at the time, which was to focus on the impact on student and teacher attitudes rather than the impact on literacy. Through the critical appraisal of current research it is revealed that the attitudes and beliefs of individual teachers to laptop integration is the leading cause of student literacy achievement. The literature review progresses to explore the challenges facing educators and the concerns for educators.